(untitled) (Bangladesh Journal of Botany, 2025)
Soybean (Glycine max L.) is valued for its high protein content and versatile applications. This study evaluated the effects of integrated nutrient management on growth, yield and yield attributes of soybean. Six fertilizer treatments such as T1 = Farmers’ improved practice (N=25, P=12, K=15, S=2 kg/ha), T2 = Recommended Dose (RD) (N = 25, P = 40, K = 45, S = 3, Zn = 1, B = 0.5 kg/ha), T3 = 50% RD + 1.2 kg/ha BINA SB-4, T4 = 100% RD + 1.2 kg/ha BINA SB-4, T5 = 100% RD (N = 5 kg/ha) + 1.2 kg/ha BINA SB-4 and T6 = 50% RD + 1.5 t/ha vermicompost, using BINA Soybean-6. The experiment was laid out in a Randomized Complete Block Design (RCBD). Results revealed that treatment T5 (100% recommended dose with nitrogen and Bradyrhizobium inoculant) achieved the highest plant height, branching, leaf count, and pod formation, resulting in superior seed yield (2.54 t/ha), stover yield (3.64 t/ha), and biological yield (6.18 t/ha). Conversely, the absence of nitrogen in T4 reduced growth and yield. The study highlighted the synergistic benefits of combining fertilizers and bio-inoculants, achieving the highest harvest index (41.08%) in T5. These findings underscore the importance of integrated nutrient management strategies for optimizing soybean production in nutrient-deficient soils. Bangladesh J. Bot. 54(1): 123-128, 2025 (March)